Designing Web-Based Mess and Dormitory Booking Applications - Darwin, Widya; Zulfadli, Zulfadli; Yuliady, Ilham; Jusmardi, Jusmardi; Deswina, Melri (Universitas Negeri Padang, 2024)
Designing a web-based mess and dormitory booking application is an innovative step in increasing the efficiency and comfort of housing services for students. This application aims to replace the manual ordering system with a web technology-based solution that makes it easier for students to access information and make reservations practically. The method used is waterfall, where the software design process is sequential which develops downwards like a waterfall and is a method suitable for use in designing systems whose specifications do not change and are systematic and sequential, so that each stage in the design process will begin when the previous stage has been completed. There are 5 stages in the waterfall method, namely analysis, design, implementation, testing, and maintenance. Allows users to easily check real-time availability, facilities and rates of mess and hostels. Through an integrated online booking system, students can make room reservations quickly, efficiently and hassle-free. The application of web technology is expected to reduce complexity in managing student housing, save time, and increase information transparency. The use of web-based Mess and Dormitory Booking Applications not only optimizes housing management, but also improves the student experience in finding housing that suits their preferences and needs. Thus, it is hoped that this application can make a positive contribution to the advancement of information technology in the academic environment and provide a modern solution for student housing needs.